The developing role of public libraries in emergency management emerging research and opportunities - Mabe, Michael (Advances in library and information science (ALIS) book series., 2017)
"[This book] is an essential reference source for the latest scholarly information on library engagement in official emergency response and how these institutions can offer community aid in disaster situations. Featuring extensive coverage on a number of topics such as hazard analysis, mitigation planning, and local command structure, this publication is ideally designed for academicians, researchers, and practitioners seeking current research on the role local businesses play in emergency response situations"--Provided by publisher.